The vocal athlete - LeBorgne, Wendy DeLeo; Rosenberg, Marci Daniels (Plural Publishing, 2019)
Written and designed to bridge the gap between the art of contemporary commercial music (CCM) singing and the science behind voice production in this ever-growing popular vocal style, this textbook is a guide for vocal pedagogy courses and speech-language pathologists, singing voice specialists, and voice teachers.